2005
DOI: 10.1002/chin.200537287
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Perspective on the Structure and Mechanism of Cytochrome P450 Enzymes

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
233
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(248 citation statements)
references
References 1 publication
13
233
0
2
Order By: Relevance
“…QM calculations on models of P450 reactions have given results that often correlate reasonably well with experimental observation (14,19,20). However, because the size of models that can feasibly be treated is limited, they may not account for important steric factors and binding preferences.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…QM calculations on models of P450 reactions have given results that often correlate reasonably well with experimental observation (14,19,20). However, because the size of models that can feasibly be treated is limited, they may not account for important steric factors and binding preferences.…”
mentioning
confidence: 75%
“…The first of these matters is determined largely by the relative abundance of the different isoforms (e.g., many drugs are oxidized by the 3A4 isoform, partly because it is very abundant), by the binding affinity of the substrate in the active site, and by distribution and P450 induction effects. Many techniques have been put forward to predict chemo-and regioselectivity, including traditional quantitative structure-activity relationship (QSAR) (9, 10) as well as three-dimensional QSAR models (10,11), construction of pharmacophore models for individual isoforms (12), substrate docking approaches using either crystal structures or homology models of the relevant enzyme (13), ab initio or density functional theory (DFT) calculations of reaction barriers and/or electronic properties (14), and rule-based methods (15). It is likely that a combination of methods will be required in general; hybrid quantum mechanical-molecular mechanics (QM/MM) methods, which allow modeling of specific effects of the protein on reactivity, have advanced to the stage where they can potentially make an important contribution (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The chemistry of CYP-enzyme-catalyzed reactions has been studied in detail, 32,33 including the properties of heme species involved in the catalytic cycle of CYPs, mechanism of alkane hydroxylation, mechanism of hydride transfer in P450nor enzyme, 34 the biosynthesis of estrogens, 35,36 and the electronic structure of the oxidizing species (Compound I) of CYPs. In a recent combined quantum chemical molecular mechanics study (QM/MM) we showed that Compound I seems to exhibit very similar properties in different CYP enzymes, implying that most likely differences in Compound I do not significantly contribute to the regioselectivity differences observed for CYPs.…”
Section: Introductionmentioning
confidence: 99%